Dinamics of the contents of the set "The world of mathematics" - Kiseliova, Danutė (Lietuvos matematikos rinkinys, 1998)
In the article is investigated the mathematics' structure for elementary classes and changes of its contents which is determined by time and ideas of general programs. There is review on basic theoretical premises, practical experience and researches, which gives influence on the content, themes, material size, methodical training appliances of the set "The world of mathematics (Matematikos pasaulyje)".